Isolation and purification of glutathione S-transferases (GSTs) from Orbicularia orbiculata / Marini binti Ibrahim - Ibrahim, Marini (2012)
Glutathione S-transferases (GSTs) in bivalves which belong to the phase II detoxification metabolism, have an advantage to be used as biomarkers of aquatic pollution. The preliminary study was to isolate and purify the GSTs from Malaysian bivalve, Orbicularia orbiculata or locally known as Siput Lala. The GST enzyme was purified by using two different matrices of affinity chromatography which were GSTrapTM HP and GSH-agarose (C3). Total proteins attained from both eluates were 0.24±0.003mg and 0.12±0.07mg for GSTrapTM HP column and GSH-agarose (C3) column, respectively. Of the enzyme activity, 18% was retained on the GSTrapTM HP column and gave purification factor of 60.2-fold. Meanwhile 16% was retained on the GSH-agarose (C3) column and gave purification factor of 89.4-fold. SDS-PAGE analysis suggested the isolated GSTs from GSTrapTM HP have two subunits molecular weight of 27 kDa and 26 kDa, while GSH-agarose (C3) eluted GSTs resulted in a band (26kDa). 2D gel analysis indicated the both matrices bound different isoforms of GST. GSTrapTM HP resolved into ten spots while GSH-agarose (C3) resolved into six spots, suggesting the variation of bound GSTs using different matrices with different length of spacer. There were six similar spots from both columns at lower molecular weight (26 kDa), meanwhile four extra spots from GSTrapTM HP appeared at higher molecular weight (27 kDa). Substrate specificities indicated that both bound GST isoforms active towards 1-chloro-2, 4-dinitrobenzene (CDNB), 3, 4-dichloronitrobenzene (DCNB) and ethacrynic acid (EA). This study had not shown the extra spots gained in GSTrapTM HP active towards other GST substrates such as 4-nitrocinnamaldehyde (NCA), trans-4-phenyl-3-butene-2-one (PBO), p-nitrobenzyl chloride (NBC) and sulfobromophthalein (BSP).